What does a practical research on teaching practice investigate? - Zavala, Ana (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2019)
This article focuses on two main topics, both related to those segments of his own teaching practice a teacher has first brought in question and then researched in a practical mode. The former refers to the theorizing nature of awareness/state a practical problem that does not refer directly to the teaching practice of the theorizing subject but rather, to a particular moment of their theorization practice with regards to their work, which we will refer to as second degree practical theorization. The latter will concern itself with observing how the researcher themselves have become the object of their own attempt to seek of new ways of understanding their professional practice, and by extension, to perhaps renew their own teaching practice. The essential invisibility of the majority of practical research processes of a given practice will entail some politically oriented reflections in the closing section.